2012
DOI: 10.1098/rspa.2011.0728
|View full text |Cite
|
Sign up to set email alerts
|

Trends, noise and re-entrant long-term persistence in Arctic sea ice

Abstract: We examine the long-term correlations and multi-fractal properties of daily satellite retrievals of Arctic sea ice albedo and extent, for periods of approximately 23 years and 32 years, respectively. The approach harnesses a recent development called multifractal temporally weighted detrended fluctuation analysis, which exploits the intuition that points closer in time are more likely to be related than distant points. In both datasets, we extract multiple crossover times, as characterized by generalized Hurst… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(40 citation statements)
references
References 25 publications
1
39
0
Order By: Relevance
“…However, the semi-variogram approach does not account for the non-stationary processes hindering detecting multiple exponents. The MF-TWDFA has previously been utilized to understand long-range correlations and multi-fractal properties in daily satellite retrievals of Arctic sea ice albedo and extent (Agarwal et al 2011(Agarwal et al , 2012. The physical length-scales detected in the MF-TWDFA and the statistical characteristics of fluctuations are the basic information underlying a core mechanism for a given phenomenon.…”
Section: Introductionmentioning
confidence: 99%
“…However, the semi-variogram approach does not account for the non-stationary processes hindering detecting multiple exponents. The MF-TWDFA has previously been utilized to understand long-range correlations and multi-fractal properties in daily satellite retrievals of Arctic sea ice albedo and extent (Agarwal et al 2011(Agarwal et al , 2012. The physical length-scales detected in the MF-TWDFA and the statistical characteristics of fluctuations are the basic information underlying a core mechanism for a given phenomenon.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study [11], we showed the effect of the presence of a strong seasonal cycle in the data on fluctuation functions. Due to the strength of the seasonal cycle, the fluctuation function saturates after the seasonal cycle timescale, thereby, masking the longer timescales that may be present in the data.…”
Section: A Point-by-point Approximation Of the Profileŷ(i)mentioning
confidence: 84%
“…Finally, it is of broad interest to understand the nature of ice decay in the Arctic. It is extremely difficult to use comprehensive GCMs to understand the qualitative distinction between the range of scenarios proposed [see Eisenman , 2012,and references therein], and extrapolation of observations on seasonal time scales is unwise [ Agarwal et al , 2012]. The simplest theoretical approaches in this field began with the two season model of Thorndike [1992], which predicts that once summer ice vanishes there is an irreversible change to the ice free state.…”
Section: Resultsmentioning
confidence: 99%